2003
DOI: 10.1053/jlts.2003.50099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience gained from the use of 120 steatotic donor livers for orthotopic liver transplantation

Abstract: Steatosis of the donor liver is known to impact on patient and allograft outcome after orthotopic liver transplantation (OLT). The aim of this study is to evaluate the effect of increasing grades of cadaveric donor liver steatosis on recipient outcome. Between January, 1986 and December, 2000, 120 OLTs were performed with 72 mild, 25 moderate, and 23 severe steatotic donor livers. Donors of steatotic livers were more likely to be older (P ‫؍‬ .001) and have died of intracerebral haemorrhage than donors of nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
180
2
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(198 citation statements)
references
References 21 publications
9
180
2
7
Order By: Relevance
“…2,[15][16][17][18][19] This incidence is similar to the one observed for our SAP group. It is worth emphasizing that the prevalence of PNF, and consequently of graft/patient losses in the SAP group, are probably overestimated due to the small sample size.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…2,[15][16][17][18][19] This incidence is similar to the one observed for our SAP group. It is worth emphasizing that the prevalence of PNF, and consequently of graft/patient losses in the SAP group, are probably overestimated due to the small sample size.…”
Section: Discussionsupporting
confidence: 90%
“…2 On these grounds, we defined suboptimal livers as those with 1 major negative factor and/or at least 2 minor factors. This definition, based on several studies published in recent years, 2,[6][7][8][9][10][11][16][17][18][19][20] revealed a statistically significant impact on post-LT graft and patient survival rates in a retrospective analysis of our last 400 cases (our unpublished data).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Terceiro, o método de investigação da esteatose hepática escolhido não é o adequado e pode limitar as conclusões referentes a este importante parâmetro. Também é verdade que resultados referentes a transplante de fígado utilizando órgãos esteatóticos são controversos 28 . Quarto, a técnica de transplante hepático utilizada na maioria dos procedimentos foi a convencional sem desvio venovenoso no qual não foi observada influência negativa na evolução pós-operatória dos receptores que receberam enxertos marginais.…”
Section: Discussionunclassified